Implicit temporal expectation attenuates auditory attentional blink. - Dawei Shen; Claude Alain (PLoS ONE, 2012)
Attentional blink (AB) describes a phenomenon whereby correct identification of a first target impairs the processing of a second target (i.e., probe) nearby in time. Evidence suggests that explicit attention orienting in the time domain can attenuate the AB. Here, we used scalp-recorded, event-related potentials to examine whether auditory AB is also sensitive to implicit temporal attention orienting. Expectations were set up implicitly by varying the probability (i.e., 80% or 20%) that the probe would occur at the +2 or +8 position following target presentation. Participants showed a significant AB, which was reduced with the increased probe probability at the +2 position. The probe probability effect was paralleled by an increase in P3b amplitude elicited by the probe. The results suggest that implicit temporal attention orienting can facilitate short-term consolidation of the probe and attenuate auditory AB.